Complex Composite Odontoma with Characteristic Histology. (15th June 2013) - Govindrajan, Sujatha; Muruganandhan, J.; Shamsudeen, Shaik; Kumar, Nalin; Ramasamy, M.; Prasad, Srinivasa
Abstract : Odontomas are the most commonly occurring odontogenic tumors, which are considered by many to be hamartomas rather than neoplasms. These clinically asymptomatic tumors are classified into complex and compound odontomas. They are usually discovered in radiographs and rarely cause bony expansion or infection. This paper discusses a case report of a complex odontoma exhibiting all the structural features and defects of enamel, dentine, and cementum in succession, with an overview on its etiology.